Surface quality study of paint stripping on aircraft skins with high energy nanosecond pulsed laser cleaning - Zhang, Hai-Xin; Hou, Ya-Chong; Li, Yun-Fei; Yang, Yun-Fei; Li, Kai; Yue, Jian-Feng; Jia, Meng-Yu; Han, Yi-Ting; Yu, Yu; Wang, Gong; Hou, Shu-Ping; Wang, Yu-Lei; et al. (Frontiers in Physics, 2025)
The aerospace sector requires materials, particularly aluminum all, to possess advanced mechanical properties for aircraft skins. Consequently, the industry implements protective coatings to counteract erosion and abrasion. Yet, as time progresses, these coatings can degrade, prompting careful paint removal to extend the longevity of aircraft. This research investigates methods to improve laser cleaning efficiency while safeguarding paint quality. It utilizes a nanosecond pulsed laser to assess factors such as laser energy, cleaning angle, and out-of-focus volume on cleaning efficacy. The findings demonstrate that the optimal energy for cleaning is 20 mJ; exceeding this threshold results in damage to the substrate. Additionally, the cleaning angle significantly impacts efficiency, with an 11° angle yielding the highest effectiveness. Manipulating the laser’s focal point also alters cleaning quality, with 30 mm providing the best outcomes. Single-point laser cleaning tests examined energy levels and cleaning cycles, highlighting that increased energy and cycles lead to surface damage and greater roughness. Furthermore, paint color affected cleaning performance, with blue paint exhibiting superior cleaning effectiveness. This study advances the development of laser cleaning methods for aircraft skins, catering to industry needs for efficient, environmentally friendly maintenance practices.